Compulsory acquisition of shares buyer, other shareholders, abuse of right of compulsory acquisition of shares - Arsić, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Company Act of Republic of Serbia includes mechanism for the compulsory acquisition of the shareholdings of minority shareholders. Technically this procedure is effected on the basis of the shareholders assembly resolution. Buyer is shareholder who has at least 90% of share capital and at least 90% of votes. Shares owned by entity under his dominant influence will be treated as shares of that shareholder provided that dominant influence exists at least one year. Company`s own shares, and shares subject o a pledge do not represent shares of other shareholders. There are several actions which may be treated as abuse of right of compulsory acquisition of shares.